ELABORAÇÃO DE UNIDADES DIDÁTICAS COMO ESTRATÉGIA CENTRAL PARA A COMPREENSÃO DOS MODELOS CIENTÍFICOS: UMA PROPOSTA BASEADA EM VIGOTSKI PARA O ESTUDO DO MOVIMENTO PONTA - Santos, Leandro Antonio dos (2016)
This master dissertation describes the process of research, development and application of four teaching units addressed to the study of motion carried out at a public high school. In the teaching units were discussed concepts such as velocity, free fall and its relationship with the study of the inclined plane, gravity acceleration, simple pendulum and finally, the principle of conservation of the linear momentum. A better understanding of the physical contents was intended by emphasizing discussions concerning to the scientific models, the possible formalization schemes and their correspondent idealizations or approximations. By applying the teaching units, methodological tools were considered in the form of computer simulations, experimental activities, documentaries and experimental video presentations. Also, discussions of solved problems, general searches and debates were enforced. The Interactionist Social Theory due Vigostski was applied as the theoretical basis for the work. From that perspective, the social interaction in the classroom was further enhancing by promoting the exchange of ideas, an active involvement of the students and a permanent dialogue, that allowed the classroom teacher to work in the zone of proximal development acting as the mediator between the previous student knowledges and the scientific knowledge to be acquired. It also is emphasized the collaborative work with others physics teachers at Nearby Pubic High Schools that allowed the improvement of the present proposal.